(untitled) (Revista de Ciências Agroveterinárias, 2008)
This work was carried out aiming to isolate microorganisms belonging to the Listeria genus. For that purpose, 161 samples of commercial colonial cheese obtained in several geographic regions of Rio Grande do Sul, from 2003 to 2006, were bacteriologicaly examined according to the official protocol of Brazilian Ministry of Agriculture. Isolated of Listeria sp. from 12 samples were examined regarding to phenotypic characteristics based on colonial morphology, elective culture media and blood agar, type of hemolysis, sugar fermentation and CAMP test. Listeria innocua was the most frequent isolate from 10 cheese samples, followed by L. monocytogenes which was isolated from 2 samples.